Improving delamination resistance through tailored defects. (1st September 2020) - Herráez, M.; Pichler, N.; Botsis, J.
Abstract: Delamination is a well-known damage mode exhibited by laminated composites which has been extensively studied in unidirectional laminates (UD). In this work, a novel strategy consisting of the introduction of a small interlaminar defect to enhance the fracture resistance to delamination of UD composites is presented. This toughening concept is based on the simultaneous propagation of multiple interlaminar cracks along different interfaces. A preliminary numerical study showed that the minimum size required by the initial defect to trigger dual propagation was 4 times the ply thickness for intermediate and thin plies for any applied mixed mode, except for pure mode II. An experimental campaign to prove the toughening concept with 1 and 3 defects at adjacent interfaces was carried out and compared against a reference configuration under three different applied mode mixities ( ϕ glob = 0.4, 0.2 and 0). The single defect configuration reached an improvement in the fracture resistance of +300% under pure applied mode I, and +80% and +100% for applied mixed modes of 0.2 and 0.4, respectively. The configuration with 3 defects reached even higher fracture toughness values: +430% in pure applied mode I, and +115% and +100% for applied mixed modes of 0.2 and 0.4, respectively. A finite element model employing cohesive zones successfully predicted both, the phenomenon of multiple crack propagation, and the effective fracture resistance of the process. Interestingly, among the dissipation mechanisms reported experimentally, the extensive promotion of fiber bridging under applied pure mode I was observed, which was not reported in the baseline configuration.